C45 ultra low k wafer technology with Cu wire bonding - Leng E.P.; Siong C.T.; Seong L.B.; Leong P.; Gunasekaran; Song J.; Mock K.; Siew C.; Sivakumar; Kid W.B.; Weily C. (2023)
As gold price continues to move in an overall rising trend, conversion to Cu wire has been given great focus as the main effort for cost reduction. Cu is a good alternative due to 26% lower electrical resistivity than Au, hence much higher electrical conductivity. However, Cu free-air-ball and bonded ball hardness are 34% and 60% higher than that of Au, hence increases the stress on bond pad and chip. Although Cu wire price is generally only 5 to 10% of Au wire cost depending on wire diameter, but bonding with a much harder material like Cu requires great characterization effort due to the a much higher level of unknowns and complexities, especially when dealing with ultra fine pitch and ultra low k wafer technology. 2010 IEEE.